Pengaruh Konsentrasi HPMC-Kitosan terhadap Sifat Fisik dan Aktivitas Antioksidan Serum Ekstrak Pegagan (Centella asiatica L. Urban) - Autri Nur Aziza; Aldi Budi Riyanta; Purgiyanti purigiyanti (Jurnal Insan Cendekia, 2022)
The use of pegagan (Centella asiatica L.) is an important spotlight in the development of pharmaceutical dosage forms, especially in the scope of cosmetic preparations. Pegagan (Centella asiatica L.) contains secondary metabolites such as flavonoids, phenolics, saponins, and steroids which are natural antioxidants from a plant. This study aims to be able to apply the benefits of pegagan (Centella asiatica L.) in the manufacture of pharmaceutical preparations in the form of facial serum made in three concentrations of HPMC as a gelling agent, namely 4%, 6%, and 8%. HPMC is a gelling agent that can affect the antioxidant value contained in topical preparations. The method in making face serum preparations of pegagan (Centella asiatica L.) extract utilizing the combination of HPMC with chitosan which both have the property of influencing the antioxidant properties of serum preparations made and measurement of antioxidant activity using the DPPH attenuation method as measure by UV-Vis spectrophotometry. The serum of pegagan (Centella asiatica L.) extract which has the best antioxidant activity is Formula 1 (F1) with an IC50 value of 110 μg/mL. F1, F2, and F3 are categories of IC50 values ​​which are included in the category of having moderate levels of antioxidant activity.